1) Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation.
(3 • (x - 1) - 2x) - 9 = 0
Solve x-12 = 0
Add 12 to both sides of the equation
x = 12
2)Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation
(5d + 4 • (3 - d)) - 36 = 0
Solving a Single Variable Equation
d - 24 = 0
Add 24 to both sides of the equation
d = 24
3) ((98 - 9y) + 10 • (y + 3)) - 213 = 0
y - 85 = 0
Solve : y-85 = 0
Add 85 to both sides of the equation :
y = 85
4)(-67c + 4 • (17c + 1)) - 768 = 0
c - 764 = 0
Solve : c-764 = 0
Add 764 to both sides of the equation :
c = 764